Examination of the Teacher Candidates’ Environmental Attitudes via NEP Scale in terms of Different Variables - Emine Hande Aydos; Esed Yağcı (Journal of Education in Science, Environment and Health)
In today’s world, the importance of environment education that is one of the most important issues is increasing rapidly. In the basis of the education, families and teachers take role together. It is aimed to grow up individuals who have positive attitudes and are sensitive the environment at every level of education. In order to achieve this goal, there is need for teachers giving importance to environment education and having adequate equipment. It will be beneficial to learn the environmental attitudes of teacher candidates who grow up elementary students after a few years. Because of this reason, in this study, it is aimed to examine the environmental attitudes of teacher candidates in terms of different variables. In the research, quantitative research methods were used. Sample is consisted of 1th and 3rd grade students from different department of science in Faculty of Education at Hacettepe University. In order to collect the data, New Environmental Paradigm (NEP) Scale was used. In the finding of the research, it was investigated that there is a difference in environmental attitudes of teacher candidates in terms of department of science, grade level, region lived during their childhood and get the status of environment education course variables and there is no difference in term of also, some suggestions were given.